PAEA Accreditation Task Force Briefing Paper: Moving Toward Profession-Defined, Outcomes-Based Accreditation. Issue 4 (December 2017) - Bondy, Mary Jo; Fletcher, Sara; Lane, Steven
Abstract : Abstract: In anticipation of a revision to the Standards for Accreditation, the Phyisician Assistant Education Association (PAEA) charged a small task force to develop a strategy for engaging its members in the revision process. Rather than focusing on the current Standards, the task force members recommend a backward design approach to determine the desired outcomes of a successful revision to the Standards. Ultimately, the group believes that shifting to a profession-defined, outcomes-based model for accreditation will allow for greater innovation in physician assistant education and reduce the strain on programs facing resource limitations, particularly clinical site shortages. Task force members value accreditation and urge a paradigm shift in the Standards revision process to focus on meaningful educational outcomes that lead to enhanced program quality and patient safety.